Exergoeconomic Analysis of an Industrial Cogeneration Cooling System Powered By Natural Gas Fueled Diesel Engine - Ceyhun Yılmaz (Düzce Üniversitesi Bilim ve Teknoloji Dergisi, 2020)
This studypresents the exergy and exergoeconomic analysis of a natural gas-powered dieselcogeneration system. The cogeneration system is designed for a sports complexwith 1000 m2 closed area in Afyonkarahisar city. Natural gas is used as thefuel in the cogeneration system of the sports complex, which includes aswimming pool and ice rink. The natural gas diesel engine is used as theprimary energy source for the cogeneration system. In the system, theelectricity required for the cooling cycle is produced from the natural gasdiesel engine. At the same time, the engine exhaust gases are used in theprocess of heat generation for swimming pool water heating. Finally, the wasteheat discharged from the system is used to produce electricity in thethermoelectric power unit. The cogeneration system was modeled thermodynamicallyby the EES program on a computer and then economically analyzed by using theAspen Plus program. The operation of thecogeneration system is described in detail, and a methodology based onexergoeconomic relations and SPECO method is provided to allocate cost flowsthrough subcomponents of the system. The results were compared by usingthermodynamic and exergoeconomic performance parameters. The exergetic efficiency of the cogenerationsystem is found to be 28.74%, which indicates that 71.26% of the total exergyinput to the system, mainly by natural gas, is destroyed. As a result of theeconomic analysis of the cogeneration system, the investment cost wascalculated as 62,000 $. The exergetic cost rate and the specific unit exergeticcost of the power produced in the cogeneration system are calculated to be 0.75$/h and 10.93 $/GJ (0.039 $/kWh), respectively. The specific unit exergeticcost of the energy produced in the cogeneration system for cooling the ice rinkand heating the swimming pool in the sports complex are calculated to be 6.152$/GJ (0.022 $/kWh) and 4.221 $/GJ (0.0152 $ /kWh), respectively.